Extending heart preservation to 24 h with normothermic perfusion - Spencer, Brianna L.; Wilhelm, Spencer K.; Stephan, Christopher; Urrea, Kristopher A.; Palacio, Daniela Pelaez; Bartlett, Robert H.; Drake, Daniel H.; Rojas-Pena, Alvaro (Frontiers in Cardiovascular Medicine, 2024)
Cold static storage (CSS) for up to 6h is the gold-standard in heart preservation. Although some hearts stored over 6h have been transplanted, longer CSS times have increased post-transplant morbimortality. Transmedics® Organ Care System (OCS™) is the only FDA approved commercial system that provides an alternative to CSS using Normothermic Ex situ Heart Perfusion (NEHP) in resting mode using aortic perfusion (Langendorff method). However, it is also limited to 6 h and lacks objective assessment of cardiac function. Developing a system that can perfuse hearts under NEHP conditions for >24h can lead to organ rehabilitation, expansion of the donor pool, and objective functional evaluation. The Extracorporeal Life Support Laboratory at the University of Michigan has worked to prolong NEHP to >24h with objective assessment of heart viability during NEHP. An NEHP system was developed for aortic (Langendorff) perfusion using blood derived perfusate (leukocyte/thrombocyte depleted blood). Porcine hearts (n=42) of different sizes (6-55 kg) have been divided into 5 groups and studied during 24h NEHP with various interventions in three piglet (small-size) heart groups: 1) Control NEHP without interventions (n=15); 2) NEHP + plasma exchange (n=5); 3) NEHP + hemofiltration (n=10); and two adult-size (juvenile pigs) hearts groups (to demonstrate support of larger hearts); 4) NEHP + Hemofiltration (n=5); and 5) NEHP with intermittent left atrial (iLA) perfusion (n=7). All hearts with NEHP + interventions (n=27) were successfully perfused for 24h, whereas fourteen (93.3%) control hearts failed between 10-21 h and one control heart (6.6%) lasted 24h. Hearts in the piglet hemofiltration and plasma exchange groups performed better than the control group. The larger hearts in the iLA perfusion group (n=7) allowed for real-time heart functional assessment and remained stable throughout the 24h of NEHP. Heart preservation for 24h is feasible with our NEHP perfusion technique. Increasing the preservation period beyond 24h, infection control and nutritional support needs optimization. This proves the concept that NEHP has the potential to increase the organ pool by 1) considering previously discarded hearts; 2) objective assessment of heart function; 3) increasing the donor/recipient distance; and 4) developing heart specific perfusion therapies.